On Infinite Horizon Optimal Stopping of General Random Walk - Jukka Lempa (Aboa Centre for Economics (ACE), 2006)
The objective of this study is to provide an alternative characterization of the optimal value function of a certain Black- Scholes-type optimal stopping problem where the underlying stochastic process is a general random walk, i.e. the process constituted by partial sums of an IID sequence of random variables. Furthermore, the pasting principle of this optimal stopping problem is studied.
Keywords: G35; G31; C44; Q23; 330; General random walk; optimal stopping; minimal functions; continuous pasting